Baseline investigation on rabies in Rangpur and Chittagong divisions, Bangladesh (Bangladesh Journal of Zoology, 2012)
Baseline investigation on rabies in Chittagong and Rangpur divisions was evaluated for the first time in Bangladesh from June 2010 to January 2011. A total of 600 respondents was interviewed including common people, school teachers, peoples' representatives, political leaders, doctors and nurses and Medical technicians from selected households. Approximately 89% of the respondents heard the name of rabies. Regionally 86% of the respondents in Rangpur division and 91% in Chittagong division possessed information fully or partly about rabies. The higher rate (91%) of respondents heard about rabies in Chittagong division and sources of respondents knowledge about rabies comprised mostly radio, TV, health worker and other sources. Approximately 100% of the respondents of different categories would seek treatment from the hospital. Majority knew about the fate of rabies that is ultimate death and believed that rabies could be prevented by vaccination program. Regarding the control of stray and poorly supervised dogs, the majority of the participants suggested for the elimination of the dogs.DOI: http://dx.doi.org/10.3329/bjz.v39i2.10586 Bangladesh J. Zool. 39(2): 195-204, 2011